Design Driven Testing Test Smarter, Not Harder - Stephens, Matt.; Rosenberg, Doug.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
The groundbreaking book Design Driven Testing brings sanity back to the software development process by flipping around the concept of Test Driven Development (TDD)$1 (Brestoring the concept of using testing to verify a design instead of pretending that unit tests are a replacement for design. Anyone who feels that TDD is (3z(BToo Damn Difficult(3y (Bwill appreciate this book. Design Driven Testing shows that, by combining a forward-thinking development process with cutting-edge automation, testing can be a finely targeted, business-driven, rewarding effort. In other words, you$1 (Bll learn how to test smarter, not harder. Applies a feedback-driven approach to each stage of the project lifecycle. Illustrates a lightweight and effective approach using a core subset of UML. Follows a real-life example project using Java and Flex/ActionScript. Presents bonus chapters for advanced DDTers covering unit-test antipatterns (and their opposite, (3z(Btest-conscious(3y (Bdesign patterns), and showing how to create your own test transformation templates in Enterprise Architect.s
DDT vs. TDD -- Somebody Has It Backwards -- TDD Using Hello World -- (3z(BHello World!(3y (BUsing DDT -- DDT in the Real World: Mapplet 2.0 Travel Web Site -- Introducing the Mapplet Project -- Detailed Design and Unit Testing -- Conceptual Design and Controller Testing -- Acceptance Testing: Expanding Use Case Scenarios -- Acceptance Testing: Business Requirements -- Advanced DDT -- Unit Testing Antipatterns (The (3z(BDon$1 (Bts(3y(B) -- Design for Easier Testing -- Automated Integration Testing -- Unit Testing Algorithms.s
Keywords: Computer science; Computer Science; Computer Science, general; Programming Techniques